2019
DOI: 10.1080/09540105.2019.1686467
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel fungal immunomodulatory protein, FIP-SJ75 shuffled from Ganoderma lucidum , Flammulina velutipes and Volvariella volvacea

Abstract: FIP-SJ75, a novel fungal immunomodulatory protein gene, was shuffled from the genes of three different mushroom species: Ganoderma lucidum, Flammulina velutipes, and Volvariella volvacea. Based on the expression of FIP-SJ75 gene in Escherichia coli, recombinant FIP-SJ75 (rFIP-SJ75) was routinely confirmed, consisting of 115 amino acids, and six peptides were identified by LC/Q-TOF MS with a coverage rate of 84.3%. Bioactivity assay in vitro indicated that rFIP-SJ75 promoted the proliferation of RAW264.7 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Many drugs are known to be immunomodulatory substances because they have significant clinical efficacy for altering host responses in the therapy of viral and bacterial infections [111][112][113][114]. Various edible mushrooms have been studied for many years in terms of the effects of their metabolites in boosting immune responses and treating infectious [115][116][117][118]. The principal immunomodulatory effect of active substances derived from mushrooms is to stimulate immune effector cells such as T cells, cytotoxic T lymphocytes (CTL), dendritic cells (DCs), lymphocytes, macrophages and natural killer (NK) cells, resulting in cytokine expression and secretion including interleukins (ILs), tumor necrosis factor-alpha (TNF)-α, and interferon-gamma (INF)-γ [119,120].…”
Section: Potential Of Fungal Bioactive Compounds For Immunomodulatorsmentioning
confidence: 99%
“…Many drugs are known to be immunomodulatory substances because they have significant clinical efficacy for altering host responses in the therapy of viral and bacterial infections [111][112][113][114]. Various edible mushrooms have been studied for many years in terms of the effects of their metabolites in boosting immune responses and treating infectious [115][116][117][118]. The principal immunomodulatory effect of active substances derived from mushrooms is to stimulate immune effector cells such as T cells, cytotoxic T lymphocytes (CTL), dendritic cells (DCs), lymphocytes, macrophages and natural killer (NK) cells, resulting in cytokine expression and secretion including interleukins (ILs), tumor necrosis factor-alpha (TNF)-α, and interferon-gamma (INF)-γ [119,120].…”
Section: Potential Of Fungal Bioactive Compounds For Immunomodulatorsmentioning
confidence: 99%
“…However, the exact underlying mechanism of DCs ( 58 , 73 ) and macrophages ( 62 ) activation by LZ-8 still needs to be further explored, especially its supposed TLR4 binding, since minor lipopolysaccharide (LPS) contamination could cause similar results in DCs and macrophages ( 74 , 75 ). FIP-SJ75, which is a chimera composed of LZ-8, FIP-fve and FIP-vvo ( 19 ), triggered similar cytokine expression profiles in macrophages as seen for LZ-8 (shown in Table 3 ). Its underlying mechanism was still unknown, which needs further investigation.…”
Section: Health-promoting Activities Of Fipsmentioning
confidence: 70%
“…In this study, the recombinant FIP-vvo proteins can enhance DC maturation and function the same as the natural FIP-vvo. Furthermore, recent studies have demonstrated that FIP-SJ75, reconstituted FIP from G. lucidum, F. velutipes, and V. volvacea, has increased immunomodulatory function on RAW264.7 macrophages [40]. Therefore, it is worthwhile to keep investigating and optimizing these FIPs.…”
Section: Discussionmentioning
confidence: 99%
“…velutipes , and V . volvacea , has increased immunomodulatory function on RAW264.7 macrophages [ 40 ]. Therefore, it is worthwhile to keep investigating and optimizing these FIPs.…”
Section: Discussionmentioning
confidence: 99%